Factors Related to the Length of Stay for Patients With Schizophrenia: A Retrospective Study - Cheng, Peng; Wang, Lirong; Xu, Lizhi; Zhou, Ying; Zhang, Li; Li, Weihui (Frontiers in Psychiatry, 2022)
Background: The length of stay (LOS) of patients with schizophrenia has been widely concerned by researchers. Reasonable management of the LOS to achieve the balance between quality of treatment and efficient medical source allocation has become a significant issue in psychiatry clinical work. Figuring out the factors related to the LOS of schizophrenia patients can optimize the management of the hospital. Method: Essential information of patients was obtained from the electronic medical record system. Variables were divided into the following kinds, demographic, clinical and biochemical. Univariate analysis and multivariate analysis were conducted to find potential factors related to the LOS of schizophrenia patients. The receiver operating characteristic (ROC) analyses were conducted to evaluate the accuracy of judging the LOS of the regression model. Result: A total of 1160 patients with schizophrenia were enrolled in our research. Our results demonstrated that the status of unmarried (single, separated, divorced or widowed) and the abnormality of TSH were risk factors for the longer LOS in schizophrenia patients. The area under the curve (AUC) was 0.576, which meant that the regression model had a certain prediction value. Conclusion: To our knowledge, this research is the first study to analyze the effect of various factors, including the biochemical index, on the LOS of a single type of mental disorder. Marital status and TSH were proved to be related to the LOS of schizophrenia patients. The results of this study provided reference factors of LOS for clinical psychiatry, which will be helpful to the management of hospitalization and optimizing the allocation of medical sources.